Prospects for the effective use of irrigated lands in Karakalpakstan in conditions of water resource scarcity - Utambetov Duysenbay; Sagidullaev Amudulla; Sadykov Esbosin; Nurullaev Fayzulla; Polatov Nursultan; Bobojonov Zafar; Sultonov Mukhammad; Normatov Rikhsimurod (BIO Web of Conferences)
Present the results of many years of development on the effective use of irrigated arable land and water resources in conditions of water shortage. At the same time, a decrease in rice content to 40% and the saturation of the crop rotation wedge with other upland grain crops leads to the gradual use of arable land up to 120% and the grain size increases to 80% relative to the opposite scheme. Reducing rice content by up to 40% on medium loamy soils, with the rice irrigation rate recommended for this zone, allows saving about 25-27% of irrigation water. The use of the recommended technology ensures an increase in rice yield within the range of 11.2 centners, winter wheat - 11.3 centners/ha. The sorghum crop additionally introduced into the scheme provided 66.4 c/ha of yield. Thanks to drip irrigation, when re-seeding after winter wheat, 24.0 tons/ha of potato yield was obtained, when using conventional technology 12.5 tons/ha were obtained. At the same time, the savings in irrigation water amounted to 50- 55%, in addition, the use of expensive mineral fertilizers was reduced by 35- 40% and plant protection products by 25-30%. Thus, in the conditions of the Republic of Karakalpakstan, the introduction of a drip irrigation system that supplies plants in accordance with their water consumption is a relevant and modern approach to the issues of saving natural resources, creating optimal water and nutrient regimes in the root layer of the soil, obtaining an early and high-quality harvest of agricultural crops, automation of irrigation processes, preservation of soil fertility and mitigation of the environmental situation of the region.